2016
DOI: 10.2337/dc16-1376
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Metabolism After Gastric Banding and Gastric Bypass in Individuals With Type 2 Diabetes: Weight Loss Effect

Abstract: OBJECTIVEThe superior effect of Roux-en-Y gastric bypass (RYGB) on glucose control compared with laparoscopic adjustable gastric banding (LAGB) is confounded by the greater weight loss after RYGB. We therefore examined the effect of these two surgeries on metabolic parameters matched on small and large amounts of weight loss.RESEARCH DESIGN AND METHODSSeverely obese individuals with type 2 diabetes were tested for glucose metabolism, β-cell function, and insulin sensitivity after oral and intravenous glucose s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 43 publications
2
29
1
Order By: Relevance
“…Gastric banding (20)(21)(22) and metformin (23,24) have been shown to improve insulin sensitivity, b-cell function, and glycemia in people with fully developed T2D. In people with IGT or early, mild T2D, we observed no improvement in b-cell function and only modest improvements in glycemia despite large improvements in insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 51%
“…Gastric banding (20)(21)(22) and metformin (23,24) have been shown to improve insulin sensitivity, b-cell function, and glycemia in people with fully developed T2D. In people with IGT or early, mild T2D, we observed no improvement in b-cell function and only modest improvements in glycemia despite large improvements in insulin sensitivity.…”
Section: Discussioncontrasting
confidence: 51%
“…We mentioned above that the glycemic improvement of restrictive procedures versus RYGB in the SOS study was similar when the participants were matched by weight loss . The same results were seen in another study in which oral and intravenous glucose tolerance tests were performed after 10% and 20% weight loss in individuals after laparoscopic adjustable gastric banding and RYGB . Although individuals undergoing RYGB had a better glucose AUC after 10% weight loss, no difference between the procedures was observed at a more pronounced 20% weight loss, despite an increased incretin effect after RYGB.…”
Section: Long‐term Weight Loss Gut Hormones Effects and Glycemic Imsupporting
confidence: 69%
“…34 The same results were seen in another study in which oral and intravenous glucose tolerance tests were performed after 10% and 20% weight loss in individuals after laparoscopic adjustable gastric banding and RYGB. 82 Although individuals undergoing RYGB had a better glucose AUC after 10% weight loss, no difference between the procedures was observed at a more pronounced 20% weight loss, despite an increased incretin effect after RYGB. Bradley et al found similar results when comparing the metabolic response, insulin sensitivity, and beta-cell function in response to a mixed meal in nondiabetics after a 20% weight loss with RYGB versus gastric banding, suggesting that weight loss was the most important driver of metabolic benefit.…”
Section: Long-term Weight Loss Gut Hormones Effects and Glycemic mentioning
confidence: 93%
“…It has some association with sensitivity in human subjects . HOMA insulin resistance (HOMA‐IR) in a type 2 diabetic group (BMI 41.8 kg/M 2 ) has been reported as 10.3 ± 7.7 while in an obese non‐diabetic group with a somewhat greater BMI (BMI 46.5 kg/M 2 ) HOMA‐IR was reported to be 5.8 ± 1.9 . The higher HOMA number in the diabetics with a lower BMI suggests greater insulin resistance in obese diabetics than is caused by the obesity.…”
Section: Introductionmentioning
confidence: 99%